Identification, cloning and expression of an insecticide cry8 gene from Bacillus thuringiensis INTA Fr7-4 - Amadio, Ariel Fernando (2013)
Insecticidal activity of Bacillus thuringiensis is attributed largely to the crystal proteins. These were found with specific toxic activity against insects in different orders. A novel cry8 gene from B. thuringiensis strain INTA Fr7-4 from Argentina was characterized. The encoded protein, Cry8Qa2, is 1184 amino acids long and its sequence is more similar to those of Cry8F class. We cloned and expressed the protein in an acrystalliferous strain of B. thuringiensis using two differentially regulated promoters. The recombinant strains produced ovoid crystals with low toxicity against larvae of Anticarsia gemmatalis (Lepidoptera: Noctuidae). The morphology and insecticidal properties of these crystals resembled those produced by the native strain INTA Fr7-4.